2014
DOI: 10.1002/ijc.28753
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus genotype 1b increases cumulative lifetime risk of hepatocellular carcinoma

Abstract: The association between subtypes of hepatitis C virus (HCV) and risk of hepatocellular carcinoma (HCC) remained inconclusive and evaluated in both case-control and cohort studies. In the case-control study, 397 HCC cases from medical centers were compared with 410 community-based non-HCC controls. All of them were anti-HCV-seropositive, HBsAg-seronegative with serum HCV RNA levels 1,000 IU/mL. Logistic regression models were used to estimate the odds ratio (OR) with 95% confidence interval (95% CI) of HCV subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 44 publications
1
45
0
1
Order By: Relevance
“…Second, HCV prevalence in all countries examined increased with advancing age, and HCV genotypes 1b and 2 were the most common genotypes among the general populations, although no recent data (2011-2014) were available for Japan or South Korea. A cohort study from Taiwan that examined the association of HCV genotypes and the risk for HCC found that HCV 1b was an independent risk factor for HCC and that genotype 1b carried a higher risk for HCC than genotype 1a [38]. In addition, it was estimated that the cumulative lifetime risk for HCC is 6.5, 19.2 and 29.7 % for those with HCV RNA levels \1000 IU/ml, HCV non-1b and HCV 1b, respectively (p \ 0.001) [38,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, HCV prevalence in all countries examined increased with advancing age, and HCV genotypes 1b and 2 were the most common genotypes among the general populations, although no recent data (2011-2014) were available for Japan or South Korea. A cohort study from Taiwan that examined the association of HCV genotypes and the risk for HCC found that HCV 1b was an independent risk factor for HCC and that genotype 1b carried a higher risk for HCC than genotype 1a [38]. In addition, it was estimated that the cumulative lifetime risk for HCC is 6.5, 19.2 and 29.7 % for those with HCV RNA levels \1000 IU/ml, HCV non-1b and HCV 1b, respectively (p \ 0.001) [38,47].…”
Section: Discussionmentioning
confidence: 99%
“…Five studies, four [7,[35][36][37] from China and one [38] from Taiwan, reported the prevalence of HCV by HCV genotype. No studies were identified that reported the prevalence of HCV by HCV genotype in Japan and South Korea.…”
Section: Prevalence Of Hcv By Genotypementioning
confidence: 99%
“…The role of genotypes 1b and 3 in increasing the risk of HCC development has been widely questioned recently and even though numerous studies have often suggested their association with the HCC carcinogenetic progression [68][69][70][71][72][73][74], especially in patients with underlying cirrhosis, [38][39][40][41][75][76][77], probably for the strict correlation existing between these subtypes and liver damage, no consensus has emerged yet. Whether HCV 1b genotype contains specific nucleotide sequences that may be associated with direct pathogenesis or may trigger a stronger inflammatory response still needs to be extensively investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Despite several published studies showing that patients infected with HCV genotype 1b may have a higher risk of developing HCC than those infected with other genotypes [39][40][41], other authors did not confirm this result [42,43]. As a consequence, no consensus has yet emerged and the role of HCV genotypes in both accelerating the progression of the disease and as a risk factor for HCC remains to be established.…”
Section: Introductionmentioning
confidence: 97%
“…In the community-based REVEAL-HBV/HCV study, HCC risk predictors for chronic hepatitis B patients include male gender, increasing age, family history of HCC, habitual alcohol consumption, HBeAg serostatus, genotype C (versus genotype B) and basal core promoter A1762T/G1764A mutant of HBV, co-infection with HCV, and elevated serum levels of HBV DNA, HBsAg and ALT [4,[7][8][9][10]. The long-term HCC risk predictors for chronic hepatitis C patients include increasing age, cirrhosis status, HCV genotype 1, elevated serum levels of HCV RNA and ALT, increased ratio between serum AST and ALT level (AST/ALT ratio), and co-infection with HBV [5,[11][12].…”
mentioning
confidence: 99%